Аналітична оцінка типу та якості економічного розвитку молочних підприємств України - Кулинич, Юрій Михайлович (My University, 2013)
У тезах розглянуто типи економічного розвитку підприємства. Запропоновано методику оцінки типу економічного розвитку. Здійснено оцінку типу економічного розвитку молочних підприємств України. Запропоновано варіанти зміни типу економічного розвитку. The theses are considered types of economic development enterprise. The methods of evaluation such as economic development. The assessment of the type of economic development of Dairy Enterprises of Ukraine. Proposed options for changing the type of economic development.
Keywords: інтенсифікація; стратегічне планування; економічний розвиток; підприємство; тип розвитку; intensification; strategic planning; economic development; enterprise; type of development; кафедра фінансів